2011
DOI: 10.1111/j.1365-2699.2011.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Discordant patterns of geographic variation between mitochondrial and microsatellite markers in the Mexican black iguana (Ctenosaura pectinata) in a contact zone

Abstract: To delimit the distribution of matrilines of the black iguana (Ctenosaura pectinata), detect potential contact zones between them, and test the hypothesis of geographic concordance in the structuring of matrilines with respect to genetic structuring across the nuclear genome. Pacific coast of Mexico in the states of Nayarit, Jalisco, Colima, Michoacán in the lowlands adjacent to the western end of the Mexican Volcanic Belt. Tissue samples were obtained every 10–20 km along a transect across the range of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 62 publications
(141 reference statements)
2
26
0
Order By: Relevance
“…Our results confirm several recent studies on squamate reptiles in which the combination of nuclear and mtDNA markers revealed discordant patterns (Renoult et al. 2009; Zarza et al. 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm several recent studies on squamate reptiles in which the combination of nuclear and mtDNA markers revealed discordant patterns (Renoult et al. 2009; Zarza et al. 2011).…”
Section: Discussionsupporting
confidence: 92%
“…It cannot be discarded that the different population differentiation scenarios depicted by microsatellites and cyt b are caused by the existence of a secondary contact scenario as suggested in the case of other species with discordant patterns of geographic variation between mitochondrial and microsatellite markers (Lu et al 2001;Zarza et al 2011). Upon secondary contact, genetically differentiated populations form hybrid zones, interbreeding to various extents, and the level and extension of gene flow for mitochondrial and nuclear genomes might differ (Toews and Brelsford 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Mitochondrial and nuclear genomes differ in size, structure, location within the cell, copy number, modes of inheritance, replication, segregation, selection pressures and recombination and mutation rates (reviewed in Ballard and Whitlock 2004;White et al 2008;Galtier et al 2009). Discordance among these markers has been reported in instances of varying historical and contemporary gene flow (e.g., Rönkä et al 2012;Zarza et al 2011), sex biased dispersal (e.g., Damm andHadrys 2012, Yannic et al 2012) or sex-based differential selection (e.g., Teske et al 2012). Although congruence among markers for pāua suggests similar dispersal and selection patterns for both males and females, further research examining genetic structure in regards to sex and other markers is necessary.…”
Section: Discussionmentioning
confidence: 95%